Head and tail pancreatic duct stones mimicking duplex staghorn renal calculi: A rare case - Yuda Handaya, Adeodatus (Int J Surg Case Rep, 2020)
INTRODUCTION: Pancreatolithiasis is an uncommon disease and the diagnosis of pancreatic duct stones is challenging. The radiological findings of pancreatic duct stones may mimic other diseases, such as renal stones. CASE PRESENTATION: A 42-year-old male came with chief complaint of recurrent bilateral flank pain accompanied by fever which worsen 7 days before admission. The patient was diagnosed as gastritis and received analgesics in several hospitals. Ultrasonography and IVP examinations showed stones in both kidneys. CT-scan was not performed due to limitation in the hospital. Patient was diagnosed bilateral staghorn nephrolithiasis. The patient underwent bilateral bivalve nephrotomy for staghorn renal stone performed by urologist, but intraoperatively, no stones were found. The patient was then consulted intraoperatively to the digestive surgeon and get immediate median laparotomy. Intraoperatively, stones were palpated in the head and tail of the pancreas. The stones were evacuated. The symptoms were relieved, neither recurrence, nor pain, nor postoperative leakage was found. Patient was discharged uneventfully 4 days after the procedure and had no complaints in further follow-ups. DISCUSSION: The symptoms of pancreatolithiasis may overlap with nephrolithiasis and gastritis. The presented case was unique because from the history taking, clinical symptoms, USG, and IVP findings supported the diagnosis of nephrolithiasis, but intraoperative findings reveal pancreatic duct stones. CONCLUSION: For patient diagnosed with renal calculi based on sonography and IVP findings, differential diagnosis of pancreatic stone should be considered especially if no underlying cause is detected. In such circumstances relying on IVP and sonographic findings alone can be misleading.